Keabsahan Surat Keputusan Bersama Untuk Penyidikan Perkara Koneksitas Pasca Perubahan Ketatanegaraan Indonesia - Hedwig Adianto Mau; Ramlani Lina Sinaulan (Universitas Jayabaya, 2021)
This study aims at post-reformation there has been a change in the state administration where the listed institutions have been independently separated, the judiciary is under the authority of the Supreme Court, the Ministry of Defense and Security has been separated into the Ministry of Defense, the Indonesian National Army and the National Police, and the Indonesian Attorney General’s Office which is independent. The problem that is studied is how the validity of the Joint Decree is, with normative juridical research methods as a means of discussion and supported by a statutory approach and a conceptual approach. This study concludes that the existence of a Joint Decree is no longer relevant because the officials who issue it do not have the authority anymore based on the laws and regulations. Thus, the Joint Decree must be revised by involving four related institutions, namely; The Supreme Court, the Indonesian National Armed Forces, the National Police, and the Indonesian Attorney General’s Office.